2022
DOI: 10.3390/toxins14050296
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Significance of the Circadian Time of Administration on the Effectiveness and Tolerability of OnabotulinumtoxinA for Chronic Migraine Prophylaxis

Abstract: We aimed to provide insights on the role of the circadian time of administration in influencing the efficacy and tolerability/safety profile of OnabotulinumtoxinA (BoNTA) for chronic migraine (CM) prophylaxis. Methods: We retrospectively reviewed the medical files of BoNTA-naïve patients with CM who completed three consecutive cycles of treatment, according to the standard PREEMPT paradigm. Participants were classified to those scheduled to be treated in the morning hours from 8:00 to 12:00 (AM) or afternoon h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Several factors have been associated with a better clinical response of OnabotA [30][31][32][33], but there is less information regarding tolerability not influenced, according to previous studies, by circadian time of administration [34] or needle length [35]. In our study, the only factor associated with a better tolerability was age.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Several factors have been associated with a better clinical response of OnabotA [30][31][32][33], but there is less information regarding tolerability not influenced, according to previous studies, by circadian time of administration [34] or needle length [35]. In our study, the only factor associated with a better tolerability was age.…”
Section: Discussioncontrasting
confidence: 66%
“…The most commonly reported treatment-related AEs were neck pain (4.4%), eyelid ptosis (4.1%), muscular weakness (2.9%), headache (2.5%), musculoskeletal stiffness (2%) and migraine (2.9%). Another large study, the COMPEL study [34], showed a treatment-related AE rate of 18.3%. The most frequent AEs in this study were neck pain (4.1%), followed by eyelid ptosis (2.5%), musculoskeletal stiffness (2.4%), pain in injection side (2%), headache (1.7%), muscular weakness (1.4%), facial palsy (1.3%), migraine (1%) and skin tightness (1%).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current national policies, full reimbursement is granted for BoNTA in the setting of CM prophylaxis to patients who fail to respond or are intolerant to three previous conventional, orally given medications. The general inclusion and exclusion criteria remained the same, as previously described by our research group [ 42 , 43 , 44 ]. Briefly, the inclusion criteria were the following.…”
Section: Methodsmentioning
confidence: 99%
“…BTX (Botox ® 100UI/fl; Allergan-Abbvie, Hellas, Greece) either as monotherapy or as part of the dual intervention was administered from certified BTX injectors at predefined cranial and cervical sites and at a fixed dose of 155-195 UI per trimester, according to our previously published experience up to 5 years of continuous (per trimester) BTX exposure [30][31][32][33]. Patients on BTX monotherapy were scheduled to receive at least three treatment cycles per trimester before defining success or failure to intervention.…”
Section: Methodsmentioning
confidence: 99%